Indonesia's Accession to the OECD: Strategic Motivation and Foreign Policy Challenges in the Era of Prabowo Subianto - Heriyana Heriyana; Istiq Agustina (Journal of Social Research, 2025)
This study analyzes the strategic motivations and challenges of Indonesia's foreign policy in its membership process in the Organisation for Economic Co-operation and Development (OECD) during the administration of President Prabowo Subianto. Indonesia views OECD membership as a crucial step to accelerate the transformation of the national economy towards developed country status by 2045 through the implementation of transparent, inclusive, and sustainable global economic governance standards. Using a qualitative approach based on an integrative literature review, this study applies theories of foreign policy analysis and rational decision-making to understand the political, economic, and strategic considerations that shape Indonesia's decision. The findings indicate that the "Prabowonomics" economic model—which emphasizes economic independence, equitable distribution of wealth, strengthening industry, and sustainable development—demonstrates strong alignment with OECD norms and objectives. Consequently, OECD membership is expected to be a key lever for increasing foreign direct investment, facilitating technology transfer, supporting structural reform efforts, and enhancing Indonesia's global competitiveness. Despite these potential benefits, the OECD membership process presents significant challenges, including the need to comply with stringent OECD regulatory standards, the potential loss of preferential trade facilities such as the United States' Generalized System of Preferences (GSP), and complex diplomatic maneuvering as Indonesia navigates its simultaneous involvement in both the BRICS and OECD frameworks. This study emphasizes the importance of domestic policy adjustments, institutional readiness, and strengthened stakeholder coordination for Indonesia to fully maximize the benefits of OECD membership. These efforts are essential to support the broader national agenda and realize the long-term vision of Golden Indonesia 2045.